La aplicación de un programa psicoterapéutico a los adolescentes infractores mientras cumplen con las medidas socioeducativas en el centro de internamiento de varones en el Cantón Machala. - Chilan Herrera, Betzabeth Liliana (2013)
I must emphasize that this research work aims to sound out with absolute precision the causes and effects , and likewise offer possible solutions to the critical problem of the lack of rehabilitation and resocialization of juvenile offenders , even become a legal mandate as constitutional , and whose principle unquestionably it has been neglected by the various presidential regimes that have administered the country until today , resulting in inexcusable detriment of society , the family.